CONTINUITY AND CHANGE IN THE PRESENTATION OF SIKAMBANG ARTS IN THE SOCIETY OF SIBOLGA CITY - Sinaga, Mario Yosua; Purba, Mauly; Nasution, Ikhwanuddin (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This study is entitled Continuity and Changes in the Presentation of Sikambang Art in the Community of Sibolga City. In this study, qualitative methods are used as a reference in conducting research. This research took place on Jalan Sisinga Mangaraja XII, Sibolga City. The purpose of this study was to determine the continuity and changes that occurred in the period before independence, after independence and the New Order era until now. In this study, researchers apply the theory of cultural change according to Herskovitz; cultural change can be seen from two points of view, namely, what happened in the past and the present. Based on the first point of view, they always use it in the term diffusion, which is defined as the transmission of culture in the process. The results achieved in this study are the dynamics of change in a period of 3 periods wherein the pre-independence stage, Sikambang art was still very simple, only played with Sikambang drums, and then in the post-independence phase, Sikambang art progressed with the addition of several instruments in its presentation. Then in the New Order phase, Sikambang art began to be eroded by the entry of new cultures, which caused a lack of interest in the new generation in maintaining Sikambang art. This can be seen from the loss of several songs in the Sikambang arts.